2021
DOI: 10.3390/su13084166
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneity Research of the Impact of EPU on Environmental Pollution: Empirical Evidence Based on 15 Countries

Abstract: While economic growth has been the main goal of countries around the world, environmental problems such as air pollution have also arisen. Since the increase in economic uncertainty is limiting production capacity and consumers’ marginal propensity to consume, which reduces CO2 emissions, economic policy uncertainty has become one of the most important factors affecting CO2 emissions. COVID-19 has demonstrated that economic policy uncertainty reduces the enthusiasm of market participants, which, in turn, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
2
14
3
1
Order By: Relevance
“…Recently, it is also found that EPU decreases the CO 2 emissions in the long-run [11]. Similarly, EPU discourages investment in R&D and renewable energy, which ultimately mitigates CO 2 emissions [12]. Regarding the literature on the relationship between GPR and environmental quality, GPR mitigates renewable energy consumption and investment in R&D. as a result, GPR leads to environmental degradation [19].…”
Section: Literature On the Impact Of Epu And Gpr On Environmental Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it is also found that EPU decreases the CO 2 emissions in the long-run [11]. Similarly, EPU discourages investment in R&D and renewable energy, which ultimately mitigates CO 2 emissions [12]. Regarding the literature on the relationship between GPR and environmental quality, GPR mitigates renewable energy consumption and investment in R&D. as a result, GPR leads to environmental degradation [19].…”
Section: Literature On the Impact Of Epu And Gpr On Environmental Degradationmentioning
confidence: 99%
“…There exist a few research outlets that explore the impact of EPU on environmental degradation. Regarding the relationship between EPU and environment, one strand of literature notes that EPU upsurges the environmental degradation [6][7][8][9], whereas second strand of literature reports that EPU plunges environmental degradation [10][11][12]. Besides, there exists a study which highlights that EPU does not affect environment [13].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that higher levels of economic policy uncertainties adversely affect CO2 emissions in Iran. This results implying that policy uncertainty may decrease or delay economic production, which in turn will cause a reduction in carbon emissions (Chen et al 2021). This result, especially for countries that have fossil fuel as a natural resource, is expected.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Adams et al (2020) stated that economic policy uncertainty might increase CO2 emissions, especially in resource-rich countries, because policy uncertainty may limit innovations to reduce energy consumption and carbon emissions. On the other hand, policy uncertainty may decrease or delay economic production, which in turn will cause a reduction in carbon emissions (Chen et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the findings of these research are contradictory and diverse, depending on the methodological techniques used and the nations studied. EPU has been shown to improve environmental quality in a number of studies (Ahmed et al 2021 ; Chu and Le 2022 ; Ivanovski and Marinucci 2021 ; Liu and Zhang 2022 ; Gu et al 2021a ; Xin and Xin 2022 ; Zeng and Yue 2022 ; Chen et al 2021 ). For example, Ahmed et al ( 2021 ) reported that EPU decreases CO 2 emissions in the USA using the nonlinear autoregressive distributed lag (NARDL) technique for the period 1985–2017.…”
Section: Literature Review and Contributions Of The Studymentioning
confidence: 99%